2022
DOI: 10.1186/s12957-022-02725-9
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node ratio is a prospective prognostic indicator for locally advanced gastric cancer patients after neoadjuvant chemotherapy

Abstract: Background The accuracy of lymph node ratio (LNR) as a prognostic index remains to be proven for gastric cancer patients after neoadjuvant chemotherapy (NACT). This study sought to investigate the prognostic value of LNR in locally advanced gastric cancer (LAGC) patients after NACT. Methods LAGC patients with clinical TNM stages 2–3, Her2(−), and Eastern Cooperative Oncology Group, scores 0–2 are routinely scheduled with NACT. Patients with LAGC af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Of the 11 cases, who were ART-0 treated with NAC, 6 were pCR, 5 were non-pCR, and 3 were ypN positive, all receiving postoperative adjuvant chemotherapy. Several studies have demonstrated that lymph node metastasis in GC is a prognostic factor after surgical resection alone (Baiocchi et al 2010;Siewert et al 1998) and NAC followed by curative surgery (Jiang et al 2022;Fukagawa et al 2018). Although the number of cases was small, the prognosis would likely be highly favorable if ART was 0 after NAC, even if ypN-positive or non-pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 cases, who were ART-0 treated with NAC, 6 were pCR, 5 were non-pCR, and 3 were ypN positive, all receiving postoperative adjuvant chemotherapy. Several studies have demonstrated that lymph node metastasis in GC is a prognostic factor after surgical resection alone (Baiocchi et al 2010;Siewert et al 1998) and NAC followed by curative surgery (Jiang et al 2022;Fukagawa et al 2018). Although the number of cases was small, the prognosis would likely be highly favorable if ART was 0 after NAC, even if ypN-positive or non-pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NACT combined with radical gastrectomy has become a standard treatment for LAGC ( 3 6 ). However, approximately 40% of gastric cancer patients treated with NACT experience recurrence and metastasis within 3 years after surgery ( 3 5 , 7 , 8 ). Therefore, exploring new models of neoadjuvant therapy for LAGC is essential.…”
Section: Introductionmentioning
confidence: 99%